Associação genética entre características de carcaça, crescimento e de reprodução em bovinos braford e brangus - Zuim, Deise Mescua (2021)
The study was developed with the objective of estimating the genetic association between growth, reproduction and carcass traits obtained by ultrasound in Braford and Brangus cattle. Longissimus muscle area (LMA), and backfat thickness (BFT), postweaning average daily weight gain (ADG), visual scores of conformation (C), precocity (P), muscling (M), size (S), scrotal circumference (SC) at around 420 and 550 days of age, and days to first calving (DFC). The heritability estimates obtained were of moderate magnitude for LMA (0.23 to 0.27) and low for BFT (0.07 to 0.16), supporting the possibility of a favorable response to selection, especially LMA. The most favorable genetic correlations found for visual scores were between P550 and LMA (0.39 to 0.51) and between M550 and LMA (0.32 to 0.41) for Braford, and for Brangus they were between P550 and LMA420 or LMA550 (0.56) and between M550 and LMA (0.17 to 0.51). Estimates of genetic correlation between BFT and P550 were positive and of moderate to high magnitude for Braford (0.33 to 0.58) and Brangus (0.26 to 0.61). The genetic associations between SC and LMA were of low magnitude, however stronger when SC was measured around 550 days for Braford (0.12 to 0.30) and Brangus (0.01 to 0.21). Between SC and BFT, the genetic correlations varied from -0.18 to -0.12 for Braford and from -0.26 to 0.42 for Brangus. There was evidence of a favorable genetic relationship of DFC with LMA (- 0.22 to -0.12) and BFT (-0.26 to -0.22) at different ages in Braford cattle, the same was not observed for Brangus for LMA (0.03 to 0.29) and BFT (0.04 to 0.57). In view of the differences in estimates of genetic correlation between breeds and measurement ages of animals, it is necessary to develop specific selection strategies for each case.